A 3D Magnetic Hyaluronic Acid Hydrogel for Magnetomechanical Neuromodulation of Primary Dorsal Root Ganglion Neurons. Issue 29 (10th June 2018) - Tay, Andy; Sohrabi, Alireza; Poole, Kate; Seidlits, Stephanie; Di Carlo, Dino
Abstract: Neuromodulation tools are useful to decipher and modulate neural circuitries implicated in functions and diseases. Existing electrical and chemical tools cannot offer specific neural modulation while optogenetics has limitations for deep tissue interfaces, which might be overcome by miniaturized optoelectronic devices in the future. Here, a 3D magnetic hyaluronic hydrogel is described that offers noninvasive neuromodulation via magnetomechanical stimulation of primary dorsal root ganglion (DRG) neurons. The hydrogel shares similar biochemical and biophysical properties as the extracellular matrix of spinal cord, facilitating healthy growth of functional neurites and expression of excitatory and inhibitory ion channels. By testing with different neurotoxins, and micropillar substrate deflections with electrophysical recordings, it is found that acute magnetomechanical stimulation induces calcium influx in DRG neurons primarily via endogenous, mechanosensitive TRPV4 and PIEZO2 channels. Next, capitalizing on the receptor adaptation characteristic of DRG neurons, chronic magnetomechanical stimulation is performed and found that it reduces the expression of PIEZO2 channels, which can be useful for modulating pain where mechanosensitive channels are typically overexpressed. A general strategy is thus offered for neuroscientists and material scientists to fabricate 3D magnetic biomaterials tailored to different types of excitable cells for remote magnetomechanical modulation. Abstract : Acute magnetomechanical stimulation using magnetic hyaluronic acid hydrogels induces calcium influx in dorsal root ganglion neurons, primarily via endogenous, mechanosensitive TRPV4 and PIEZO2 channels. The magnetic hydrogel is easily synthesized, and can be lyophilized, transported, and reconstituted conveniently. Its mechanism does not require exogenous gene transfection typically through viral vectors and is arguably more clinically friendly by avoiding potential adverse immune reactions.